'The body remembers': narrating embodied reconciliations of eating disorder and recovery. Issue 1 (2nd January 2016) - Eli, Karin
ABSTRACT: After severe illness, there are stories: narrative strands to suture discontinuities of identities, practices, and lives. But within these narratives of illness and recovery, the body's discontinuities stand apart, striking in the materiality of change, in the tangible multiplicity of bodies – healthy, ill, recovering, recovered – that a person can call one's own. Based on longitudinal research interviews with Israeli women who identified as recovered from long-term eating disorders (fieldwork conducted in 2005–2006 and in 2011), this paper explores how these bodily discontinuities are expressed, drawing particular attention to the narrative role of embodied memory in linking past and present-tense bodies and selves. Embodied memory, as narrated by the participants, is deeply, sometimes surprisingly, embedded in lived experience, imbuing recovered bodies with moments of sensory continuity, the past coming into presence through forms of sensation and perception learned at the height of disorder. Examining narrative moments of sensory remembrance, this paper analyses how participants narrate embodied memory as a mode of reflection, self-protection, and dynamic integration, wherein the experience of disorder informs practices of recovery, and the body becomes a site for the reconciliation of past and present.